Behind intention and behaviour: factors influencing wine consumption in a novice market. Issue 3 (7th March 2016) - Agnoli, Lara; Capitello, Roberta; Begalli, Diego
Abstract : Purpose: – The purpose of this paper is to advance the understanding of the decision-making process of consumers from novice markets facing the choice of a complex product like wine, explaining the determinants of their consumption intention and behaviour. It also aims to understand the link between product attributes and consumption intention and behaviour, analysing the role played by intrinsic and extrinsic cues. Design/methodology/approach: – This study applies the theory of planned behaviour considering that individuals do not always have complete control of wine consumption behaviour, especially when they come from a novice market. A questionnaire survey, preceded by an exploratory phase, was conducted in St Louis, Missouri, a novice market for wine. Findings: – This study identifies a novice consumer whose choice of a complex product is driven by experiential attitude towards the product more than the conditioning of referents, and even more than the perceived behavioural control and the interconnected concept of risk. The risk is perceived to a greater extent when it has to do with the functional nature of the product linked to its sensory component, rather than with its social or health connotations. Originality/value: – This study assesses the role of intrinsic and extrinsic cues and of the perceived behavioural control, assumed as closely interconnected with the concept of risk, in explaining wine consumption intention and behaviour. Perceived behavioural control was omitted by previous studies applying the reasoned action approach to explain wine consumption behaviour.